Tradisi dan Makna Simbolis Payung Geulis dalam Masyarakat Sunda - Maharani, Intan; Ramadani, Tria; Sabila, Zahra Salsa; Nugraha, Ghenia Tasya; Hidayat, Rizky Achmad; Apriani, Mutia; Humairah, Mina Kameliya; Putri, Zahra Amelia; Gustaman, Randy Fadilah; Rosita, Lilis (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/ Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
Abstract. Cultural heritage is an object or intangible attribute that is the identity of a community or people inherited from previous generations that are preserved for future generations. One unique cultural heritage is the geulis umbrella in the Tasikmalaya area. The geulis umbrella has a distinctive design with beautiful traditional decorations and a deep symbolic meaning. This research aims to explore the cultural heritage of geulis umbrellas in the Tasikmalaya area, including the history, production process, meaning and symbols of the images made and their role for life. The research methods used are direct observation, interviews with geulis umbrella craftsmen, and literature study to obtain comprehensive information. The results showed that the geulis umbrella is a cultural heritage of Tasikmalaya with a long history and symbolic meanings in its motifs, such as prosperity and harmony. Its production process is traditional and passed down through generations, making it a cultural identity used in various traditional events. In addition to its aesthetic value, the geulis umbrella has the potential to support the creative economy and tourism sectors. However, challenges such as the regeneration of young artisans and modern competition require promotional efforts and design innovations to preserve its sustainability.